Crystallization behavior of poly(ε-caprolactone)/layered double hydroxide nanocomposites - Yang, Zhe; Peng, Hongdan; Wang, Weizhi; Liu, Tianxi (Journal of applied polymer science, 2010)
Poly(ε-caprolactone) (PCL)/layered double hydroxide (LDH) nanocomposites were prepared successfully via simple solution intercalation. The nonisothermal melt crystallization kinetics of neat PCL and its LDH nanocomposites was investigated with the Ozawa, Avrami, and combined Avrami-Ozawa methods. The Ozawa method failed to describe the crystallization kinetics of the studied systems. The Avrami method was found to be useful for describing the nonisothermal crystallization behavior, but the parameters in this method do not have explicit meaning for nonisothermal crystallization. The combined Avrami-Ozawa method explained the nonisothermal crystallization behavior of PCL and its LDH nanocomposites effectively. The kinetic results and polarized optical microscopy observations indicated that the addition of LDH could affect the mechanism of nucleation and growth of the PCL matrix. The Takhor model was used to analyze the activation energies of nonisothermal crystallization.